The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1177/1054773815573261
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Activities of Daily Living Among Older People One Year After Hip Fracture

Abstract: This article aims to determine the functional recovery of older people, who were previously independent in activities of daily living (ADLs) and without cognitive impairment, in the year following a fall-related hip fracture. A cohort study was carried out among patients admitted to University General Hospital of Albacete (Spain). Consecutive sampling was performed. Variables included demographic, habitual residence, type of hip fracture, mental status (Short Portable Mental Status Questionnaire [SPMSQ] Pfeiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 30 publications
3
23
1
Order By: Relevance
“…The proportions fully recovering post-surgery in our study were consistent with previous research [ 7 , 13 , 14 , 25 ]. According to a review by Dyer et al [ 7 ], about 30% of HF patients did not regain their pre-fracture level of independence in ADL.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The proportions fully recovering post-surgery in our study were consistent with previous research [ 7 , 13 , 14 , 25 ]. According to a review by Dyer et al [ 7 ], about 30% of HF patients did not regain their pre-fracture level of independence in ADL.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have identified specific demographic or health pre-operative indicators, as well as operative and post-operative predictors of long-term functional outcome among older HF patients who underwent surgical treatment. Age, gender, pre-fracture functioning, health status, including cognitive status, and fracture type are the most common patient-related factors [ 3 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPMSQ is quick and easy to administer and well suited for screening large populations for cognitive status and severity of deficit [34]. The SPMSQ has been used in several studies [10, 20, 35, 36].…”
Section: Methodsmentioning
confidence: 99%
“…Patients with impaired cognitive status also have a poorer short-term and long-term postoperative outcome after hip fracture than patients with intact cognition [19]. In this case, outcome is defined as a decrease in postoperative recovery relating to activities of daily living (ADL), quality of life and mobility [20], increased length of hospital stay and mortality [21]. The perioperative period is defined as the time periods immediately before, during and following a surgical operation [22].…”
Section: Introductionmentioning
confidence: 99%